Diretrizes normativas e legais para aquisição de luminárias viárias com diodo emissor de luz pelas administrações municipais em ambiente sustentável - Funchal, Ronaldo Silveira (2017)
The application of LED technology in street lighting is recent in Brazil, raising doubts in the specification, acquisition, economic and environmental viability. With the adoption of LED street lighting, bids must meet the new technical specifications, maintenance should be modified and disposal of withdrawals lamps should minimize environmental impact. An analysis of the technological evolution of public lighting and the legislation and standards for the implementation of LED technology is presented, as well as an evaluation of the technical requirements for the specification of luminaries. The bidding process and cases of dispute involving public LED lamps is discussed. To support the study, the feasibility analysis is performed in which sodium vapor lamps are replaced by solid-state lamps in a square located in Tres Passos-RS. The main results of modernization and technological advance are the reduction in the monthly bill of energy, greater durability, lower maintenance due to the reduction in lamp exchanges, improvement in levels of brightness and environmental benefits such as the reduction of the carbon dioxide equivalent indicator and mercury contamination. The contribution of this work is to present the guidelines to specify LED public lighting, meeting the legal and regulatory requirements in force, serving as a reference for local public officials involved in public lighting.